Study on the Interfacial Curvature of Oil-Water Two Phase System subjected to Polymeric Additives - Gwee , Yong Ling (IRC, 2016)
During the transportation of well fluids to refinery plant, drag which is also known as resistance will occur due to the friction between the pipelines and the fluids. Several pumping stations need to be installed along the pipelines due to the pressure drop which eventually increase the cost of transportation. Thereafter, Toms - a researcher in UK has discovered in 1949 that the injection of polymeric drag reducing additives (DRA) can increase the flow rate in the pipeline significantly which had bring a huge contribution to the flow assurance sector. The drag reducing agent which is the polymer solution has the ability to change the flow properties of the medium during the fluids transportation. It also altered the interfacial curvature of oil-water phases which causing the flow rate to be increased.